Preventive but Not Therapeutic Topical Application of Local Anesthetics Can Inhibit Experimental Epidermolysis Bullosa Acquisita in Mice - Wen, Lifang; Dong, Xiaoru; Li, Qing; Schramm, Gabriele; Zhang, Bing; Zillikens, Detlef; Ludwig, Ralf J.; Petersen, Frank; Yu, Xinhua (Frontiers in Immunology, 2021)
Epidermolysis bullosa acquisita (EBA) is an autoimmune blistering disorder characterized and caused by autoantibodies against type VII collagen (COL7). Although it has been noticed that EBA in both patients and mice is associated with an increased scratching, it is not clear whether and how the scratching contributes to disease manifestation. Hence, we here aimed to validate this clinical observation and also to investigate the potential contribution of increased scratching in EBA pathogenesis in mice. Longitudinal assessment of scratching behavior revealed an increased frequency of scratching as early as 12 hours after injection of anti-COL7 IgG into the skin of mice. Subsequently, scratching events became even more frequent in mice. In contrast, mice injected with a control antibody showed an unaltered scratching behavior throughout the observation period. Based on these observations, we hypothesized that mechanical irritation may promote the induction of inflammation in experimental EBA. To challenge this assumption, the local anesthetic dyclonine hydrochloride was topically applied before injection of anti-COL7 IgG. Dyclonine hydrochloride reduced the scratching events and impaired clinical disease manifestation. In therapeutic experimental settings, i.e. administration of the local anesthetic 24 hours after injection of anti-COL7 IgG, dyclonine hydrochloride only inhibited the scratching behavior, but had no significant effect on clinical disease development. In addition, eosinophils were detected in the skin before the injection of anti-COL7 IgG and significantly increased 48 hours after the antibody injection. Collectively, our results suggest that scratching behavior contributes to the initiation phase of disease manifestation in experimental EBA.